Effects of L-Theanine and L-Arginine supplementation on attention, cognitive, and shooting performance in elite air rifle shooters - Buzdagli, Y.; Canyurt, F.; Inaç, M. R.; Ozan, M.; Çaglar, B.; Köse, D. (International Journal of Sport and Exercise Psychology, 2026)
This study aimed to investigate the acute effects of L-theanine (L-THE), L-arginine (L-ARG), and their combined supplementation on shooting performance, cognitive function, and attention in elite air rifle shooters. Fifteen elite female 10-m air rifle shooters participated in a randomised, double-blind, placebo-controlled, crossover study. Participants completed four experimental conditions: placebo (PLA), L-THE, L-ARG, and combined L-THE*L-ARG. Sixty minutes after supplementation, the d2 Attention Test and Stroop Colour - Word Test were administered, followed by a standardised 60-shot air rifle performance trial in accordance with International Shooting Sport Federation (ISSF) rules. L-THE and combined L-THE*L-ARG supplementation significantly improved shooting performance compared with placebo, with the highest scores observed in the combined condition. Stroop test results indicated that reaction times were reduced under L-THE supplementation and were fastest in the combined group. The d2 Attention Test revealed improvements in processing speed, net performance, and concentration, together with reductions in error and fluctuation rates; these effects were again most pronounced under combined supplementation. L-THE supplementation improved both cognitive performance and shooting accuracy in elite air rifle athletes. Although the effect of L-ARG alone was limited, its co-administration with L-THE produced greater synergistic benefits. These findings suggest that L-THE and L-ARG may serve as potential ergogenic aids in sports requiring sustained attention and fine motor control.